2006
DOI: 10.1159/000093481
|View full text |Cite
|
Sign up to set email alerts
|

Anthroposophische Medizin: Health Technology Assessment Bericht – Kurzfassung

Abstract: The aim of this Health Technology Assessment Report was to analyse the current situation, efficacy, effectiveness, safety, utilization, and costs of Anthroposophic Medicine (AM) with special emphasis on everyday practice. Design: Systematic review. Material and Methods: Search of 20 databases, reference lists and expert consultations. Criteriabased analysis was performed to assess methodological quality and external validity of the studies. Results: AM is a complementary medical system that extends conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 19 publications
0
34
2
5
Order By: Relevance
“…Anthroposophical medicine as an IM system is based on scientific standards and guidelines of conventional medicine but integrates a range of treatment options like naturopathy remedies and non-pharmacological interventions (NPIs), including mindfulness-orientated movement therapies (e.g., eurythmy therapy), mind-body procedures, art therapies, and nursing interventions [9,16,17,18,19,20]. The aim is to promote the physical and psychological salutogenic powers and resources of the patient, to improve the health-related quality of life (HRQL) and to support social and spiritual needs.…”
Section: Introductionmentioning
confidence: 99%
“…Anthroposophical medicine as an IM system is based on scientific standards and guidelines of conventional medicine but integrates a range of treatment options like naturopathy remedies and non-pharmacological interventions (NPIs), including mindfulness-orientated movement therapies (e.g., eurythmy therapy), mind-body procedures, art therapies, and nursing interventions [9,16,17,18,19,20]. The aim is to promote the physical and psychological salutogenic powers and resources of the patient, to improve the health-related quality of life (HRQL) and to support social and spiritual needs.…”
Section: Introductionmentioning
confidence: 99%
“…16 The use of CAM in Switzerland, its efficacy, appropriateness, and cost-effectiveness have been evaluated within the frames of a federal program (Complementary Medicine Evaluation Program, PEK), which revealed that CAM was associated with a higher patient satisfaction, weaker=less frequent side-effects, and lower costs than conventional medicine (CM). 15,[17][18][19][20] The use of CAM by children in Switzerland has just started to be unveiled. A previous study performed at the intensive care unit of the Children's Hospital of Zurich revealed that 18% of the parents of critically ill pediatric patients applied some form of CAM.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the international increase in IC provision in general, and the recent juridical efforts to promote increased pluralism in Swedish health care in particular [9,10], it is crucial that such developments adhere to evidence-informed health care decision-making in order not to become more costly and less efficient for health care systems. Despite the prevalence of anthroposophic IC services, with approximately 30 hospitals and over 140 anthroposophic outpatient clinics in Europe and internationally [11], the clinical and cost effectiveness remain largely unexplored as there are only a few economic studies [12]. This situation has contributed to the sometimes negative criticism of anthroposophic IC services and its rationale including the lack of its evidence base [13].…”
Section: Introductionmentioning
confidence: 99%